Platform Pembelajaran Berbasis Digital - Novri Gazali; Leni Apriani; Alfi Candra; Sri Wahyuni; Alvi Renanda; Cendra, Romi (Universitas Nusantara PGRI Kediri, 2022)
This community service activity aims to improve the ability or skills of teachers in using digital-based learning platforms, both online and offline at SD 011 Beringin Jaya Kec. Sentajo Raya Kab. Kuantan Singingi, Riau Province. This community service activity was carried out on teachers as participants, totaling 16 people. The implementation method has two stages, namely: (1) Preparation Stage. The preparation stage carried out includes: interviews with the school, namely the teacher to determine the problems that occur during the teaching and learning process, Preparation of service materials / materials, which include: online and offline learning platforms that are suitable and easy to apply by elementary school children. (2) Service Implementation Stage. The stages in the implementation of the service are carried out online using Google Meet. Each teacher will get a link to enter or join the training. Meanwhile, to carry out these activities, three training methods were used, namely: (1) Demonstration: this was chosen to provide an explanation of the concept of online and offline learning, starting from the definition, benefits, advantages and disadvantages of online and offline learning. (2) Implementation stage: this method is used to provide knowledge and or skills in using online learning platforms and offline learning platforms using applications that have been adapted to the abilities of elementary school children. (3) Discussion: this is done to provide opportunities for teachers who do not understand the material and or the benefits of the application in the teaching and learning process. The expected outcomes in this community service activity are: (1) Improving the ability and skills of teachers in using learning platforms, (2) Publication in the Community Service Journal. The results of the activities for teachers are very helpful in increasing their knowledge about the use of digital-based learning platforms.